Effects of spatial augmented reality assistance on the efficiency of prefabricating timber frame walls - Bartuska, Birger; Teischinger, Alfred; Riegler, Martin (Wood material science and engineering, 2023)
Assistance systems have the potential to support workers in various assembly tasks. Especially in mass customized prefabrication, the correct objects need to be selected and positioned accurately. Using conventional paper plans as assembly guidance, skilled workers need to spend precious time carefully reading plans for the individually designed elements. Augmented reality (AR) systems can help to integrate information for assembly tasks directly into the work environment, which should improve time efficiency and error rates. However, AR systems are often not ergonomic or accurate enough (e.g. smartglasses) or expensive (e.g. laser projectors). In the present study, the effect of a simple projection based spatial augmented reality (SAR) system was studied for building prefabricated wall elements under laboratory conditions, using printed CAD drawings as reference. Each subject built a timber frame wall element with dimensions close to reality. Using the SAR system, the completion times were reduced by nearly 50%, the error rate of subjects with a low experience level decreased and the reported task load measured according to the NASA raw task load index using the SAR system was significantly lower.